MEMAHAMI PERKEMBANGAN MINAT KALIGRAFI DI KALANGAN ANAK DALAM SENI PENDIDIKAN ISLAM SANTRI MADRASAH ASY-SYIFA - Alissa Sefira Farhani; Muhammad Fahmi Fauzi; Reviliani; Ghania Iqlima, Zsazsa; Rudi Nurjaman, Asep (Yayasan Zia Salsabila, 2024)
This study explores fostering children's interest in calligraphy within an Islamic educational framework. By investigating factors influencing children's engagement with calligraphy and effective strategies for enhancing their appreciation for this art form, it aims to contribute to understanding and promoting calligraphy among young Muslims. Employing a descriptive qualitative approach, the research delves into participants' experiences and perceptions through questionnaires and interviews. The study involved students and teachers at Asy-Syifa Madrasah in Bandung Regency, Indonesia. Calligraphy, defined as the art of writing or drawing combining Arabic letters with intricate designs, serves as a means of conveying Allah's revelation. Findings indicate children possess an inherent interest in calligraphy, but lack opportunities for in-depth learning within the school curriculum due to constraints such as limited time, resources, and distractions. Modernization, coupled with a lack of understanding of calligraphy's value and parental support, poses challenges to sustaining children's interest. To address this, structured learning programs, opportunities for exploration, and adequate resources are proposed. Such efforts aim to enable children to recognize calligraphy's artistic and religious significance, fostering a deeper appreciation for this traditional art form within an Islamic context.